Emergence of collective oscillations in adaptive cells - Shou-Wen Wang; Lei-Han Tang (Nature Communications, 2019)
There are many examples of cell populations exhibiting density-dependent collective oscillatory behaviour. Here, the authors show that sustained collective oscillations emerge when cells anticipate variation in signal and attempt to amplify it, a property that can be linked to adaptation.